2016
DOI: 10.1177/1934578x1601101218
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites from Astragalus lycius and Their Cytotoxic Activities

Abstract: O-β-D-glucopyranoside (8) by spectroscopic methods including 1 Hand 13 C-NMR and HR-MS experiments, and by comparison with literature values. Compounds 1-7 are reported for the first time from Astragalus taxa. All of the compounds were tested for their cytotoxic activities against a number of cancer cell lines. Among them, only 6 exhibited significant activity against human colon carcinoma (HT-29) at 2.69 M concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Annexin-V/PI double staining demonstrated that SF(3) tumor growth inhibitory effect on HCT116 cells was associated to the induction of apoptotic cell death. In fact, as observed in Figure 3A, 15.84 µg/mL (twice the GI 50 ) of SF (3) induced early and late apoptosis. Western blot analysis showed that the SF (3)-induced apoptosis in HCT116 cells was associated with an increase in p53 protein, up-regulation of Bax (a p53 downstream pro-apoptotic target of the Bcl-2 family), as well as occurrence of PARP cleavage (a result of caspase-3 activation) (Figure 3B).…”
Section: Composition Of Sfs and Biological Activity In Hct116 Cellsmentioning
confidence: 52%
See 1 more Smart Citation
“…Annexin-V/PI double staining demonstrated that SF(3) tumor growth inhibitory effect on HCT116 cells was associated to the induction of apoptotic cell death. In fact, as observed in Figure 3A, 15.84 µg/mL (twice the GI 50 ) of SF (3) induced early and late apoptosis. Western blot analysis showed that the SF (3)-induced apoptosis in HCT116 cells was associated with an increase in p53 protein, up-regulation of Bax (a p53 downstream pro-apoptotic target of the Bcl-2 family), as well as occurrence of PARP cleavage (a result of caspase-3 activation) (Figure 3B).…”
Section: Composition Of Sfs and Biological Activity In Hct116 Cellsmentioning
confidence: 52%
“…Other than cell membrane permeabilization, these compounds have shown cholesterol-binding, antiviral, immunomodulatory, antimicrobial, cytostatic, and antitumor activity [1,[11][12][13]. Different studies reported the ability of saponins, in particular triterpenoid saponins, to inhibit the proliferation of several tumor cell lines through induction of cell cycle arrest and/or apoptosis [1,5,9,[11][12][13][14][15]. Moreover, it has been shown that saponins can also have nongenotoxic and non-cytotoxic effects in human lymphocytes [16,17].…”
mentioning
confidence: 99%
“…Astragalus species have saponins, flavonoids, phenylpropanoids, alkaloids, steroids, and polysaccharides and show anti-inflammatory, immunoregulatory, anti-tumour, antioxidative, antidiabetic, antiviral, and hepatoprotective activities ( Li et al, 2014 , Yang et al, 2013 ). In the literature, many studies have shown that Astragalus species and their active compounds exhibit cytotoxic effects on colon carcinoma (HCT-116, HT-29), hepatocellular carcinoma (HEPG2), myeloid leukaemia (K 562), lymphocytic leukaemia (SKW-3), osteosarcoma (MG63), and breast cancer (MCF-7, MDA-MB-231) cell lines ( Ibrahim et al, 2013 , Horo et al, 2016 , Salem et al, 2020 , Ionkova et al, 2010 ). Astragalus globosus Vahl (syn.…”
Section: Introductionmentioning
confidence: 99%
“…The known metabolites were identied as 2-phenylethyl-b-Dglucopyranoside (4), 21 stachyline C (5), 22 3-methoxy-4-hydroxyphenylethanol (6), 23 3-hydroxy-4-methoxy-phenylethanol (7), 24 p-hydroxyphenethyl alcohol (8), 25 (5R,7S)-5,7-dihydroxy-2-methyl-5,6,7,8-tetrahydro-4H-chromen-4-one (11), 20 (5R,7S)-5,7-dihydroxy-2-propyl-5,6,7,8-tetrahydro-4H-chromen-4-one (12) 20 by comparison of their NMR and MS data with those reported. Compounds 1-12 were evaluated for anti-inuenza A virus (IAV), anti-Zika virus (ZIKV), and antibacterial activities.…”
mentioning
confidence: 99%